DOI: 10.33015/dominican.edu/2017.bio.07
|View full text |Cite
|
Sign up to set email alerts
|

Changing Antimalarial Drug Sensitivities in Uganda

Abstract: None of the work contained in this thesis would have been possible without the help and support of the members of the Cooper and Rosenthal Labs, the TOLAB team members, or the study participants and their families. Special thanks to Frida Ceja for helping me collect the phenotypic drug sensitivity data in Uganda; Patrick Tumwebaze, Oswald Byaruhanga, and Thomas Katairo for their support collecting and analyzing data in Uganda; Melissa Conrad for being a great genotyping and research mentor; and Jenny Legac for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
5

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 10 publications
4
41
5
Order By: Relevance
“…Previous studies indicated that dihydroartemisinin-piperaquine treatment selected the N86Y allele in pfmdr1 in Uganda [48,[52][53][54], albeit one study questioned this association [55]. Approximately one third of parasites possessed the N86Y in 2010-2013 in Tororo [9], which was much higher than that found in our study area (2%). Since N86Y is associated with chloroquine resistance, it might be plausible that the N86Y mutation selected by piperaquine played a role in the slower recovery of chloroquine sensitivity in Tororo.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Previous studies indicated that dihydroartemisinin-piperaquine treatment selected the N86Y allele in pfmdr1 in Uganda [48,[52][53][54], albeit one study questioned this association [55]. Approximately one third of parasites possessed the N86Y in 2010-2013 in Tororo [9], which was much higher than that found in our study area (2%). Since N86Y is associated with chloroquine resistance, it might be plausible that the N86Y mutation selected by piperaquine played a role in the slower recovery of chloroquine sensitivity in Tororo.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast to chloroquine, average lumefantrine IC 50 values in the present analysis (21-29 nM) were considerably higher than those in Eastern Uganda (3.0-5.4 nM) [9,24]. It has been suggested that decrease in lumefantrine susceptibility are associated with wild type alleles in pfcrt and pfmdr1 [48,[56][57][58][59].…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations